Respuesta :
Replace x in each equation with 4:
f(x) = x^2 +2x-3 = 4^2 + 2(4) -3 = 16 + 8 -3 = 21
g(x) = x^2-9 = 4^2 -9 = 16-9 =7
Now you have values for f(x) and g(x) now you can solve for f/g and f+g:
f/g = 21 / 7 = 3
f+g = 21 + 7 = 28
For this case, we have that by definition:
[tex](f + g) (x) = f (x) + g (x)\\(\frac {f} {g})(x) = \frac {f (x)} {g (x)}[/tex]
We have the following functions:
[tex]f (x) = x ^ 2 + 2x-3\\g (x) = x ^ 2-9[/tex]
So:
[tex](f + g) (x) = x ^ 2 + 2x-3 (x ^ 2-9)\\(f + g) (x) = x ^ 2 + 2x-3 x ^ 2-9\\(f + g) (x) = 2x ^ 2 + 2x-12\\(f + g) (4) = 2 (4) ^ 2 + 2 (4) -12\\(f + g) (4) = 2 * 16 + 8-12\\(f + g) = 32 + 8-12\\(f + g) (4) = 28[/tex]
On the other hand:
[tex](\frac {f (x)} {g (x)}) = \frac {x ^ 2 + 2x-3} {x ^ 2-9}\\Evaluated\ at\ x = 4[/tex]
[tex](\frac {f (x)} {g (x)}) = \frac {4 ^ 2 + 2 (4) -3} {4 ^ 2-9} = \frac {16 + 8-3} {16 -9} = \frac {21} {7} = 3[/tex]
Answer:
[tex](f + g) (4) = 28\\(\frac {f} {g}(4)) = 3[/tex]